Glia in Health and Disease 2020
DOI: 10.5772/intechopen.89170
|View full text |Cite
|
Sign up to set email alerts
|

The Enteric Glial Network Acts in the Maintenance of Intestinal Homeostasis and in Intestinal Disorders

Abstract: The enteric nervous system (ENS), also known as second brain, innervates our gastrointestinal tract controlling its functions, such as motility, fluid secretion, nutrient absorption, and even involvement in the control of immunity and inflammatory processes. In the gut, the gliocytes are known as enteric glial cells (EGCs). Enteric glial cells form a network that permeates the entire gut. Enteric glia express the cell surface hemichannel of connexin-43 (Cx43) necessary for the propagation of Ca2 + responses, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 160 publications
(211 reference statements)
0
3
0
Order By: Relevance
“…To fully understand the enteric system's contribution to the pathophysiology of SARS-CoV-2 infection, the importance of the gut-brain axis should be considered. The so-called gutbrain axis is highly important in many disorders that affect the CNS, and several recent studies have shown the relevance of this communication for the clinical manifestation and even for the genesis of numerous diseases (Coelho-Aguiar et al, 2019). This communication would make it possible to stimulate specific centers in the CNS (Coelho-Aguiar et al, 2015).…”
Section: Potential Contribution Of the Ens To Sars-cov-2 Mechanisms And The Covid-19 Gastrointestinal Symptomsmentioning
confidence: 99%
“…To fully understand the enteric system's contribution to the pathophysiology of SARS-CoV-2 infection, the importance of the gut-brain axis should be considered. The so-called gutbrain axis is highly important in many disorders that affect the CNS, and several recent studies have shown the relevance of this communication for the clinical manifestation and even for the genesis of numerous diseases (Coelho-Aguiar et al, 2019). This communication would make it possible to stimulate specific centers in the CNS (Coelho-Aguiar et al, 2015).…”
Section: Potential Contribution Of the Ens To Sars-cov-2 Mechanisms And The Covid-19 Gastrointestinal Symptomsmentioning
confidence: 99%
“…In addition to the transcribial route and the olfactory nerve, the virus may use other peripheral nerves such as the vagus nerve, which lungs and gut afferents reach the brainstem (32,51). The gutbrain axis is a key component involved in disorders that affect the CNS (52). Interestingly, SARS-CoV-2 was detected in COVID-19 patient feces (53).…”
Section: Transcribial Route and Neuronal Transport Disseminationmentioning
confidence: 99%
“…Constipation is a common functional GI disorder characterized by infrequent bowel motions and/or incomplete defecation [ 31 ]. Constipation may arise due to loss of glial cells, and it points to a pathophysiological condition since the glial cells directly regulates enteric neurons and interstitial cells of Cajal through neurotrophic factors and ATP signaling [ 32 ].…”
Section: Discussionmentioning
confidence: 99%